The Autospreader Flap for Midvault Reconstruction following Dorsal Hump Resection - Moubayed, Sami P.; Most, Sam P. (Facial Plastic Surgery, 2016)
Dorsal hump reduction without adequate reconstitution of the midvault can often result in cosmetic or functional problems. One of the simplest techniques to avoid these problems is the use of the excess upper lateral cartilage to reconstruct the midvault (the spreader flap or autospreader). Herein we outline the history of the technique and present the specific indications and contraindications, as well as describe our method for achieving it successfully. Case studies are presented with the specific indications. Grafting alternatives to the spreader flap are also outlined. The spreader flap technique offers multiple advantages, including maximal use of local tissues, simplicity, and airway preservation. Disadvantages are the use of an external approach and the inability to use it alone in the presence of severe asymmetries.
Keywords: rhinoplasty; internal valve; autospreader; spreader flap